Light limitation regulates the response of autumn terrestrial carbon uptake to warming - Zhang, Yao; Commane, Róisín; Zhou, Sha; Williams, A. Park; Gentine, Pierre (Nature climate change, 2020)
Global warming is projected to shift the phenology and increase the productivity of northern ecosystems 1 – 6 . Both changes will further feed back to climate through biophysical and biogeochemical processes and are critical for future prediction 7 , 8 . However, it remains unclear whether warming and the extended growing season, especially in autumn, would lead to increased net ecosystem carbon uptake 9 , 10 . Here we analyse satellite observations, field measurements and model simulations and show a prevalent radiation limitation on carbon uptake in northern ecosystems, especially in autumn. By comparing the start and end of the growing season estimated from vegetation indices and from solar-induced chlorophyll fluorescence (a proxy for gross primary production 11 , 12 (GPP)), we find a greater change in greenness-based start and end of season than that from GPP, mostly caused by the radiation limitation on photosynthesis. This radiation limitation explains the contrasting responses of autumn net carbon exchanges to warming, using both eddy covariance measurements and model simulations from Coupled Model Intercomparison Project Phase 5. Regions with weak radiation limitation benefit more from warming and enhanced vegetation greenness in autumn, where GPP increases can outweigh the warming-induced respiration carbon losses. With continued warming, radiation limitation will increase and exert a strong upper bound on northern ecosystems to act as carbon sinks. Phenological shifts due to warming extend the growing season for plants, with implications for ecosystem productivity. Carbon uptake through photosynthesis is limited by radiation, particularly in autumn, which explains contrasting regional responses of autumn carbon uptake to rising temperatures.